Effect of lubrication on the nano-structure of soft metals - Peh, Jasper Jun Ming (Nanyang Technological University, 2020)
Nanowires of metallic structures are continuously researched upon due to their potential applications in wide-ranging applications. In particular, this report focuses on the formation on aluminum nanowires, and the effects of lubrication on the fabrication process. The fabrication will be carried out by imprint anodized aluminum oxide template aluminum sheets. Anodized aluminum oxide is chosen due to its repeatability and range of pore diameters. The experiments will involve the use of Carbon-60 fullerene as the lubricating substance, due to its ability to enter the pores of the anodized aluminum oxide template. Similar experiments will be conducted with varying imprinting forces and lubrication concentration to determine the optimum parameters in the fabrication process. Preliminary findings suggest some correlation in the use of the lubrication to the improvement of nanowires fabricated.